Overexpression of Adenylyl Cyclase Encoded by the Mycobacterium tuberculosis Rv2212 Gene Confers Improved Fitness, Accelerated Recovery from Dormancy and Enhanced Virulence in Mice - Shleeva, Margarita O.; Kondratieva, Tatyana K.; Demina, Galina R.; Rubakova, Elvira I.; Goncharenko, Anna V.; Apt, Alexander S.; Kaprelyants, Arseny S. (Frontiers in Cellular and Infection Microbiology, 2017)
Earlier we demonstrated that the adenylyl cyclase (AC) encoded by the MSMEG_4279 gene plays a key role in growth resuscitation of dormant Mycobacterium smegmatis and that overexpression of this gene resulted in intracellular cAMP concentration increase preventing transition of M. smegmatis from active growth to dormant state in prolonged stationary phase accompanied by medium acidification. We surmised that the homologous Rv2212 gene of M. tuberculosis (Mtb), the main cAMP producer, plays similar physiological roles, supporting the active state under such conditions and reactivation of dormant bacteria. To test this hypothesis, we established Mtb strain overexpressing Rv2212 and compared its in vitro and in vivo growth characteristics with the control strain. In vitro, AC-overexpressing pMindRv2212 strain demonstrated faster growth in liquid medium, prolonged capacity to form CFUs and significant delay or even prevention in transition towards dormancy. AC-overexpressing cells exhibited easier recovery from dormancy. In vivo, AC-overexpressing bacteria demonstrated significantly higher growth rates (virulence) in the lungs and spleens of infected mice compared to the control strain, and, unlike the latter, killed mice of TB-resistant strain before month 8 of infection. Even in the absence of selecting hygromycin B, all pMindRv2212 CFUs retained the Rv2212 insert during in vivo growth, strongly suggesting that AC overexpression is beneficial for bacteria. Taken together, our results indicate that cAMP controls maintenance of Mtb cells vitality under unfavorable conditions in vitro and virulence in vivo.